Peritoneal dialysis per se is a risk factor for sclerostin-associated adynamic bone disease - Oliveira, Rodrigo A. de; Barreto, Fellype C.; Mendes, Monique; Reis, Luciene M. dos; Castro, Joao Henrique [UNESP]; Britto, Zita Maria L.; Marques, Igor D. B.; Carvalho, Aluizio B.; Moyses, Rosa M.; Jorgetti, Vanda (Nature Publishing Group, 2015)
Chronic kidney disease-mineral bone disorder (CKD-MBD) is a complex syndrome influenced by various factors, such as age, CKD etiology, uremic toxins, and dialysis modality. Although extensively studied in hemodialysis (HD) patients, only a few studies exist for peritoneal dialysis (PD) patients. Since most of these older studies contain no bone biopsy data, we studied the pattern of renal osteodystrophy in 41 prevalent PD patients. The most common presentation was adynamic bone disease (49%). There was a significant inverse association between serum sclerostin (a Wnt/beta-catenin pathway inhibitor that decreases osteoblast action and bone formation) and the bone formation rate. Bone alkaline phosphatase had the best sensitivity and specificity to detect both high-and low-turnover diseases. The comparison between nondiabetic PD and HD patients, matched by age, gender, parathyroid hormone level, and length of dialysis, revealed low 25-hydroxyvitamin D levels, worse bone mineralization, and low bone turnover in the nondiabetic PD group. Thus, adynamic bone disease was the most frequent type of renal osteodystrophy in PD patients. Sclerostin seems to participate in the pathophysiology of adynamic bone disease and bone alkaline phosphatase was the best serum marker of bone turnover in these patients.
Keywords: Chronic kidney disease; Diabetes; Mineral metabolism; Peritoneal dialysis; Vascular calcification